Developmental competence of immature oocytes aspirated from antral follicles in patients with gynecological diseases - Fereshteh Safian; Mohammad Ali Khalili; Mojgan Karimi-Zarchi; Mehdi Mohsenzadeh; Sareh Ashourzadeh; Marjan Omidi (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2015)
Background: In vitro maturation (IVM) of immature oocytes collected from ovary has been proposed for fertility preservation. In addition, quality of oocytes post IVM is one of the factors determining its developmental competence. By using the non-invasive Polscope system, both meiotic spindle (MS) and zona pellucida (ZP) can be assessed in living oocytes. Objective: The aim was to investigate the developmental potential of immature oocytes retrieved from ovarian tissue after IVM, as a method for fertility preservation, in patients with gynecological diseases. Materials and Methods: The ovarian cortex from 26 patients with malignant and benign diseases (21-45 years old), were obtained directly from collaborating hospitals, and transported to the IVF center on ice. In total 61 immature oocytes were aspirated, of which 18 (29.5%) were degenerated and discarded. The remaining 43 (70.5%) healthy oocytes were cultured in IVM culture media for 48 hr. The rate of maturity was assessed, and the ZP birefringence and MS were imaged with Polscope technology. Results: Overall 43 immature oocytes underwent IVM technology, of which 30.2% reached viable metaphase II (MII) oocytes. The ovarian tissues of 9 (34.6%) women were lacking oocytes at any stage. During polarized light microscopy examination, MS could be visualized only in one of the MII oocytes, but high ZP birefringence's were observed in the majority of the oocytes post IVM (61.5%). Conclusion: Oocytes maturation post IVM from unstimulated ovaries showed a good developmental competence in gynecologic patients. Further studies should be performed to advance the oocyte maturation program, such as co-culture system, for fertility preservation.